Prototype Alat Pegering Kaos Kaki Prototype Of Sock Drying Machine - Try Wahyuni; Endah Fitriani (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Socks are essential daily wear that require special care, including an effective drying process to prevent unpleasant odors and the growth of bacteria and fungi. Conventional drying methods often face challenges, especially in high-humidity environments or during unfavorable weather conditions. This study aims to design and develop a prototype sock dryer that is more efficient and hygienic. The prototype utilizes a combination of a heater, UV lamp, and humidity and temperature sensors to ensure optimal drying without damaging fabric fibers. A microcontroller-based control system using Arduino Uno is implemented to regulate device operation and monitor sock conditions during drying. Testing results indicate that the device effectively dries cotton socks in damp conditions faster than conventional methods. Additionally, the sterilization feature with a UV lamp helps reduce the risk of microbial growth. This innovation is expected to provide users with a practical, hygienic, and efficient way to dry socks without depending on weather conditions. Further development can be carried out to enhance drying capacity and energy efficiency.